Greenlandic Inuit show genetic signatures of diet and climate adaptation - Fumagalli, Matteo; Moltke, Ida; Grarup, Niels; Racimo, Fernando; Bjerregaard, Peter; Jørgensen, Marit E; Korneliussen, Thorfinn S; Gerbault, Pascale; Skotte, Line; Linneberg, Allan; Christensen, Cramer; Brandslund, Ivan; et al. (Science (American Association for the Advancement of Science), 2015)
The indigenous people of Greenland, the Inuit, have lived for a long time in the extreme conditions of the Arctic, including low annual temperatures, and with a specialized diet rich in protein and fatty acids, particularly omega-3 polyunsaturated fatty acids (PUFAs). A scan of Inuit genomes for signatures of adaptation revealed signals at several loci, with the strongest signal located in a cluster of fatty acid desaturases that determine PUFA levels. The selected alleles are associated with multiple metabolic and anthropometric phenotypes and have large effect sizes for weight and height, with the effect on height replicated in Europeans. By analyzing membrane lipids, we found that the selected alleles modulate fatty acid composition, which may affect the regulation of growth hormones. Thus, the Inuit have genetic and physiological adaptations to a diet rich in PUFAs.